Thomas & friends. Engine friends [videorecording (DVD)] - Mitton, David; Asquith, Steve; Baldwin, Alec, 1958-; Carlin, George; Brandon, Michael, 1945- (HIT Entertainment ; Distributed by Lionsgate, 2012)
All aboard for epic stories of friendships on the rails: learn how Thomas met his best friend Percy for the first time and how Edward helped save Trevor the Tractor Engine from being scrapped. Join the Really Useful Engines and see when Toby showed how being helpful is the most fun, and when the unlikely duo of Emily and Whiff coupled up and became firm friends! Journey along with Thomas and the rest of the Steam Team to experience the adventures that led to fast friendships.